TREATMENT OF PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE IN REAL CLINICAL PRACTICE ACCORDING TO THE DATA FROM PROGNOZ IBS REGISTER. (Part 1) - S. N. Tolpygina; Yu. N. Polyanskaya; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии, 2015)
According to the data from PROGNOZ IBS register drugs with proven efficacy in secondary prevention of cardiovascular complications (antiplatelets, β-blockers, ACE inhibitors, statins) were not often prescribed in patients with stable ischemic heart disease prior to hospitalization. Significant improvement of the treatment quality was found during the cardiology hospital stay. The prescription rate of ACE inhibitors increased from 20% to 84.4%, statins - from 10% to 85.5%, β-blockers - from 20% to 91%, acetylsalicylic acid - from 74% to 96%. However, some drugs (statins) have been used in inadequate doses. Low-density lipoprotein level <2.5 mmol/L was achieved at discharge only in 6.3% of patients.